A study to assess the etiology, risk factors, distribution, characteristics and outcome of multisystem inflammatory syndrome in children in Hadoti region of Rajasthan - Jain, Divya; Khandelwal, Sunita (International Journal of Contemporary Pediatrics, 2022)
Background: Aim and objectives of the study was to assess the etiology, risk factors, distribution, characteristics and outcome of multisystem inflammatory syndrome in children (MIS-C) in Hadoti region of Rajasthan. Methods: A cross-sectional study was conducted, based on notified suspected cases of MIS-C with COVID-19. The records were then classified according to the definition of a ‘confirmed case. Treatment was also recorded immunoglobulin, antibiotics, corticoid, anticoagulant and oxygen supplementation. The outcome of the subjects was also recorded. Results: Majority of the subjects belonged to 1-6 years (56.6%) with 62.3% males and 37.7% females. Fever, rashes, cough, vomiting, abdominal pain, throat pain, hematuria and decreased appetite was present among 100.0%, 47.2%, 37.7%, 39.6%, 22.6%, 15.1%, 13.2% and 3.8% respectively. C-reactive protein, D-dimer, erythrocyte sedimentation rate (ESR), ferritin and lactate dehydrogenase (LDH) were present among 94.3%, 92.5%, 88.7%, 75.5% and 60.4% respectively. Discharge against medical advice (DAMA) was done for 5.7%, death among 7.5%, discharge among 84.9% and 1.9% were referred to higher centre. Conclusions: The risk of mortality was greater in MIS-C patients in LMICs despite reduced rates of ICU hospitalisation and use of mechanical ventilation. For the causation, ideal preventative and treatment strategies, and long-term results of the MIS-C patients, further proof is required.